Microstructural Characterization of Martensitic Stainless Steel Blades Manufactured by Directed Energy Deposition (DED) - Caroline Cristine de Andrade Ferreira; Rafael Humberto Mota de Siqueira; Johan Grass Nuñez; Fábio Edson Mariani; Reginaldo Teixeira Coelho; Daolun Chen; Milton Sérgio Fernandes de Lima (Metals)
This study explores the feasibility of manufacturing martensitic stainless steel turbine blades via a directed energy deposition (DED) process using a powder precursor. Five different blade geometries were fabricated using AISI 431 L martensitic stainless steel deposited onto an AISI 304 L austenitic stainless steel substrate. The produced components were characterized in terms of microstructure, surface roughness, porosity, hardness, and residual stresses in both the as-processed condition and after heat treatment at 260 and 593 °C. Optical and scanning electron microscopy (SEM) analyses revealed a predominantly martensitic microstructure with well-defined grain boundaries. Heat treatment influenced the phase distribution and grain size, but did not have a significant impact on the surface roughness or modulus of elasticity. Tomographic assessments confirmed the absence of aligned or coalesced pores, which are critical sites for crack initiation. Residual stress analysis indicated the presence of compressive stresses in all blade geometries, which were effectively relieved by heat treatment. In addition, salt spray corrosion tests demonstrated that the corrosion resistance of the manufactured blades was similar to that of the base material. These findings suggest that DED is a viable technique for producing and repairing turbine blades, providing structural integrity and mechanical properties suitable for high-performance applications.